2023
DOI: 10.1001/jamaophthalmol.2023.2097
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of 0.01% and 0.02% Atropine for the Treatment of Pediatric Myopia Progression Over 3 Years

Abstract: ImportanceThe global prevalence of myopia is predicted to approach 50% by 2050, increasing the risk of visual impairment later in life. No pharmacologic therapy is approved for treating childhood myopia progression.ObjectiveTo assess the safety and efficacy of NVK002 (Vyluma), a novel, preservative-free, 0.01% and 0.02% low-dose atropine formulation for treating myopia progression.Design, Setting, and ParticipantsThis was a double-masked, placebo-controlled, parallel-group, randomized phase 3 clinical trial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Nonetheless, the observation of increased risks for MMD with atropine concentrations of 0.1% and 0.5% deserves additional research. Of note, the 0.01% concentration used in many current studies did not show any increase in adverse events …”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Nonetheless, the observation of increased risks for MMD with atropine concentrations of 0.1% and 0.5% deserves additional research. Of note, the 0.01% concentration used in many current studies did not show any increase in adverse events …”
mentioning
confidence: 52%
“…These initial study results led to the widespread administration and rapid adoption of nightly administration of low-dose atropine eye drops (0.01% to 0.05%) to young children with low myopia (−1 diopter [D] to −6 D) to slow progression of the myopia and axial elongation of the eye. More recently completed studies in Australia, North American, and Europe have found smaller or no effects of the low concentrations studied (0.01% and 0.02%) in terms of slowing myopia progression . Each of these randomized clinical trials was launched recognizing that the primary and secondary outcomes would necessarily be short term and thus would be unable to provide the long-term outcomes needed to completely assess efficacy and safety.…”
mentioning
confidence: 99%
“…However, other similar randomized clinical trials by the National Eye Institute-sponsored Pediatric Eye Disease Investigator Group did not show a benefit of 0.01% atropine compared with placebo and suggested evaluation of the use of higher concentrations . While a Cochrane meta-analysis further supports that low dose atropine (less than 0.1%) had a mean treatment difference of 0.24 D with equivalence criteria being less than 0.25 D, these studies do not incorporate the recent lack of an effect for the primary 0.02% atropine trial by Zadnik et al nor the lack of an effect of the 0.01% atropine dose in the Pediatric Eye Disease Investigator Group.…”
Section: Discussionmentioning
confidence: 90%
“…After stopping atropine for 2 years, there was a reverse concentration-related effect suggested with greater rebound noted, especially in higher concentrations and younger children, which negated the initial benefits of atropine use . Zadnik et al also recently reported reduction in myopia progression in their secondary outcome of 0.01% atropine compared with placebo but not for the primary outcome of 0.02% atropine over 3 years of treatment. However, other similar randomized clinical trials by the National Eye Institute-sponsored Pediatric Eye Disease Investigator Group did not show a benefit of 0.01% atropine compared with placebo and suggested evaluation of the use of higher concentrations .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation